Gabapentin Does Not Appear to Improve Postoperative Pain and Sleep Patterns in Patients Who Concomitantly Receive Regional Anesthesia for Lower Extremity Orthopedic Surgery: A Randomized Control Trial. (27th February 2017) - Eloy, Jean Daniel; Anthony, Christy; Amin, Shawn; Caparó, Moorice; Reilly, Mark C.; Shulman, Steven
Abstract : In recent years, gabapentin has gained popularity as an adjuvant therapy for the treatment of postoperative pain. Numerous studies have shown a decrease in pain score, even with immediate postoperative activity, which is significant for early post-op ambulation and regaining functionality sooner. However, studies have been in conclusive in patients undergoing lower extremity orthopedic surgery. For this reason, we hoped to study the effect of gabapentin on postoperative pain in patients undergoing total knee arthroplasty, total hip arthroplasty, or a hip fracture repair. This was done in the setting of ensuring adequate postoperative analgesia with regional blocks and opioid PCA, as is protocol at our institution. Given the sedative effects of gabapentin and the potential for improving postoperative sleep patterns, we also studied the drug's effect on this aspect of our patient's postoperative course. We utilized the Pittsburg Sleep Quality Index and Visual Analog Scale for pain to obtain a more objective standardized score amongst our study population. Our results indicate that gabapentin does not offer any additional relief in pain or improve sleep habits in patients who have received either a femoral or lumbar plexus block for lower extremity orthopedic surgery. This trial is registered with NCT01546857 .